2022
DOI: 10.1016/j.isci.2021.103670
|View full text |Cite
|
Sign up to set email alerts
|

ACE2-IgG1 fusions with improved in vitro and in vivo activity against SARS-CoV-2

Abstract: SARS-CoV-2, the etiologic agent of COVID-19, uses ACE2 as a cell entry receptor. Soluble ACE2 has been shown to have neutralizing antiviral activity but has a short half-life and no active transport mechanism from the circulation into the alveolar spaces of the lung. To overcome this, we constructed an ACE2-human IgG1 fusion protein with mutations in the catalytic domain of ACE2. A mutation in the catalytic domain of ACE2, MDR504, significantly increased binding to SARS-CoV-2 spike protein, as well as to a spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Also, Zhang et al [129] reported no observable toxicity when sACE2v.2.4 was intravenously administered (twice daily at 0.5 mg/kg) into mice for 5 continuous days. Several other research have consistently found no adverse effect with the use of ACE2 therapeutics [83] , [106] , [115] , [160] , [170] , [209] . Although higher-level clinical assessments are yet to surface, it is anticipated that the human origin of the ACE2 molecule itself may be important for their safe administration.…”
Section: Outlook and Conclusionmentioning
confidence: 81%
“…Also, Zhang et al [129] reported no observable toxicity when sACE2v.2.4 was intravenously administered (twice daily at 0.5 mg/kg) into mice for 5 continuous days. Several other research have consistently found no adverse effect with the use of ACE2 therapeutics [83] , [106] , [115] , [160] , [170] , [209] . Although higher-level clinical assessments are yet to surface, it is anticipated that the human origin of the ACE2 molecule itself may be important for their safe administration.…”
Section: Outlook and Conclusionmentioning
confidence: 81%
“… [ 74 ] MDR504 WT (H345A) 740 LALA b N.D. 3.5nM c 7.5nM c (WT) Ad5-hACE2-transduced/K18-ACE2 mice, Wuhan, pre-/post-infection, 15/30 mg/kg i.v. [ 79 ] WT (H374N/H378N) N.A WT 8.23 a 1.59 a (WT) 4.17 1.02 (WT) Ad5-hACE2-transduced mice, Wuhan, pre-/post-infection, 50mg/kg i.p. [ 73 ] T27W-foldon (WT) 615 WT 0.06 76.8 (WT) 0.21 24.1 (WT) [ 72 ] D30E-tetramer/hexamer (WT) 740 WT N.D. 0.07/0.06 nM 0.68 nM (WT) [ 69 ] a Avidity value of ACE2 dimer with collectrin domain and/or Fc.…”
Section: Ace2 Mutagenesis Approaches To Achieve Increased Affinitymentioning
confidence: 99%
“…The half-life of rhACE2 (i.e., non-Fc fusion) is reported to be ~3 h in humans [ 32 , 33 ]. However, fusion with wild-type IgG1-Fc and LALA-mutated Fc extended the half-life to 30–145 h in mice [ 24 , 74 , 79 ]. Lung distribution was also sufficient to achieve effective neutralization [ 24 , 79 ].…”
Section: Antiviral Effects Of Ace2 Decoy Receptors In Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations